2010
DOI: 10.1590/s1980-65232010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Repair of amalgam restorations with conventional and bonded amalgam: an in vitro study

Abstract: Purpose: This study evaluated microleakage on amalgam restorations repaired by amalgam and bonded amalgam.Methods: Thirty extracted human pre-molars were restored by amalgam. A simulated defect was prepared and assigned to two treatment groups (n=15): G1 -repaired by amalgam (Permite C-SDI); G2 -repaired by bonded amalgam (Caulk 34% Tooth Conditioner Gel -Dentsply + Prime & Bond 2.1 -Dentsply + Permite C-SDI). The teeth were immersed in a 50% silver nitrate solution, thermocycled and then, sectioned longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…14,[16][17][18][19][20][21] This approach allows preservation of sound tooth structure. 22,23 Clinical studies involving composite resin repairs have shown that when properly planned, the repairs may increase the clinical longevity of restorations, representing a conservative choice for treatment of restorations. 13,14,24 Thus, once in vitro studies suggest that bonding of silorane-based composites to old dimethacrylatebased composites may be a viable clinical procedure, [25][26][27] it would be desirable to evaluate the clinical performance of this new system for making repairs.…”
Section: Introductionmentioning
confidence: 99%
“…14,[16][17][18][19][20][21] This approach allows preservation of sound tooth structure. 22,23 Clinical studies involving composite resin repairs have shown that when properly planned, the repairs may increase the clinical longevity of restorations, representing a conservative choice for treatment of restorations. 13,14,24 Thus, once in vitro studies suggest that bonding of silorane-based composites to old dimethacrylatebased composites may be a viable clinical procedure, [25][26][27] it would be desirable to evaluate the clinical performance of this new system for making repairs.…”
Section: Introductionmentioning
confidence: 99%
“…After the final setting of the restorative materials, all the teeth were immersed in 1% India ink dye (AB Chemi, Glasco, UK) and in the dye solution the teeth were subjected to thermocycling at 4° ± 2°C and 56° ± 2°C for 500, 2 min cycles with a dwell time of 60 s for 7 days. [2]…”
Section: Methodsmentioning
confidence: 99%
“…concept of minimally invasive restorative dentistry, total replacement should be avoided, except in cases where a fracture in the composite, discoloration of the resin contact surface with the tooth, and secondary caries are observed (7). This method helps to preserve healthy dental tissues (8).…”
mentioning
confidence: 99%
“…Brosh et al indicated that devising a single bond between the old and the new composite during the repair process is attainable through three respective mechanisms, namely (a) chemical bond to the organic matrix, (b) chemical bond to the exposed fillers, and (c) micromechanical trap (8). Preceding studies have determined the efficacy of micromechanical traps created by diamond milling, sandblasting, or acid etching in the bond strength of repaired composites (14).…”
mentioning
confidence: 99%